PENGARUH PERBEDAAN MEREK DAN SUHU PENYEDUHAN TERHADAP AKTIVITAS ANTIOKSIDAN TEH TUBRUK (Camellia sinensis L.) - Aisyah Saputri; Irvia Resti Puyanda (Jurnal BETAHPA, 2023)
One type of plant that is popular to drink is tea. From the polyphenolic compounds of this plant species containing antioxidant flavonoids are derived. The purpose of this study was to determine the total phenolic content and determine the antioxidant activity of ten brands of tea from Surakarta which were produced by the steeping process. Antioxidant activity was measured using the FRAP method and the DPPH method, and total phenol could be tested using the Follin-Ciocalteu method. The results showed that the highest total phenol was in the GP brand at 15.04% at a brewing temperature of 70°C and at 100°C with the GP brand at 24.46%, while the lowest phenol content was 7.20% at a brewing temperature of 70 °C with the 99 tea brand and at a brewing temperature of 100°C it was 7.94% with the PC tea brand. The highest samples of antioxidants using the DPPH method were steeping brand 999 at 70°C of 83.00% and steeping GP brand at 100°C of 78.70%. From the results of research conducted antioxidant testing using the FRAP method showed that the highest antioxidant activity of brewed tea at 100°C was 21.65% at 2T tea brand and the lowest antioxidant activity was brewed tea with PC tea brand at 8.87% at 70 °C and 100°C have the same value.